(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
The issue that this study addresses is to find out why students in D classes (form one D; two D; three D and four D) historically perform poorly in class and eventually in Kenya Certificate of Secondary Education (KCSE) compared to other classes in the school. To address this problem, the purpose of this study will be to discover why this particular stream historically performs dismally. To gather data, a questionnaire was administered to 52 students. The questionnaires were coded and analyzed. This data lead to the following five themes: school administrative support, self-efficacy, teachers, the other streams of students and parent involvement. These themes will be useful for understanding why this group of students performs poorly.